Smart E-learning – from the concept to practice - Pavliuk, U. V.; Yarkun, V. I.; Storozhuk, O. L. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
This work revealed that implementing Smart E-learning as one of the components of Smart Campus increases the efficiency of the educational process and provides an interactive and personalized learning environment. It was established that the key technologies that support this concept are cloud computing, IoT, artificial intelligence, and augmented reality. It was found that using these technologies contributes to improving the collection, analysis and use of data for making management decisions in the educational process. The impact of integrating modern technologies on the interaction between students and teachers was assessed, which allows optimization of the management of educational resources and increases students' motivation for learning. It was confirmed that the implementation of Smart E-learning contributes to the development of independent and research skills in students. It was confirmed that the implementation of Smart E-learning contributes to achieving sustainable development goals and increasing the overall efficiency of educational institutions.